Comparison of Mediterranean diet compliance between European and non-European populations in the Mediterranean basin. (1st December 2016) - Benhammou, Samira; Heras-González, Leticia; Ibáñez-Peinado, Diana; Barceló, Carla; Hamdan, May; Rivas, Ana; Mariscal-Arcas, Miguel; Olea-Serrano, Fatima; Monteagudo, Celia
Abstract: Fruit, vegetables, cereals, and olive oil are common elements of the Mediterranean diet (MD), but each country in the Mediterranean basin has its own gastronomic customs influenced by socio-cultural, religious, and economic factors. This study compared the dietary habits of three Mediterranean populations with different cultures and lifestyles, a total of 600 adults (61.9% females) between 25 and 70 yrs from Spain, Morocco, and Palestine. All participants completed a self administered questionnaire, including sociodemographic and anthropometric items, a validated semi-quantitative food frequency questionnaire adapted to the foods consumed in each country, and three 24-h recalls. MD adherence was estimated with the MD Serving Score (MDSS). All populations showed a moderate adherence to the Mediterranean dietary pattern. In comparison to the Palestine population, MDSS-assessed adherence to the MD was 6.36-fold higher in the Spanish population and 3.88-fold higher in the Moroccan population. Besides the country of origin, age was another predictive factor of MD adherence, which was greater (higher MDSS) in participants aged over 50 yrs than in those aged 30 yrs or younger. This preliminary study contributes initial data on dietary differences between European and non-European countries in the Mediterranean basin. The Spanish diet was shown to be closer to MD recommendations than the diet of Morocco or Palestine. Given the impact of good dietary habits on the prevention of chronic non-transmittable diseases, health policies should focus on adherence to a healthy diet, supporting traditional dietary patterns in an era of intense commercial pressures for change.